On Λ-Type Duality of Frames in Banach Spaces - Renu Chugh; Mukesh Singh; L. K. Vashisht (International Journal of Analysis and Applications, 2013)
Frames are redundant system which are useful in the reconstruction of certain classes of spaces. The dual of a frame (Hilbert) always exists and can be obtained in a natural way. Due to the presence of three Banach spaces in the definition of retro Banach frames (or Banach frames) duality of frames in Banach spaces is not similar to frames for Hilbert spaces. In this paper we introduce the notion of Λ-type duality of retro Banach frames. This can be generalized to Banach frames in Banach spaces. Necessary and sufficient conditions for the existence of the dual of retro Banach frames are obtained. A special class of retro Banach frames which always admit a dual frame is discussed.